Analisis Kemampuan Literasi Matematis Pada Materi Sistem Persamaan Linear Dua Variabel Berdasarkan Jenis Kelamin - Baiq Hana Febriana; Sudi Prayitno; Ratna Yulis Tyaningsih (Mandalika Mathematics and Educations Journal, 2026)
Mathematical literacy is an important ability that enables students to formulate, apply, and interpret mathematics in various real-life contexts. This study aims to analyze students' mathematical literacy skills on the material of Two-Variable Linear Equation Systems based on the gender of class VIII students of SMPN 2 Mataram. This study uses a descriptive qualitative approach. The research subjects consisted of 37 class VIII A students, then two male students and two female students were selected as research subjects based on test results. Data collection techniques were carried out through tests and interviews. Data analysis was carried out based on six indicators of mathematical literacy, namely communication, representation, mathematization, designing problem-solving strategies, use of operations and symbolic language, and reasoning and giving reasons. The results showed that both male and female students had good mathematical literacy skills, but there were differences in presenting answers. Male students tended to be stronger in oral explanations but less in written answers, while female students were more careful, systematic, and consistent in written solutions. This difference indicates that variation in ability is more evident in the accuracy and method of solution delivery. This research demonstrates the need to implement more inclusive and differentiated learning strategies.